Non-heterosexual ageing - Majka-Rostek, Dorota (Instytut Socjologii Uniwersytet Wrocławski, 2014)
The article concerns elderly lesbians and gays, who are an underrepresented group in social research in the area of LGBT issues. Since respondents for research are often recruited in community clubs and bars or via websites, the majority of interviewees are young or middle-aged. However, research in this field is steadily increasing, since the ageing of modern western societies pertains also to the LGBT population. In this article I firstly review recent research related specifically to elderly gays and lesbians. These are only western data, as no work has been done on this issue in Poland so far. Next I discuss selected aspects of elderly people’s functioning within the Polish LGBT community. At the end of the article I present an illustration of the issue taken from literature, i.e. the image of gay ageing in Michał Witkowski’s novel Lovetown.
Keywords: lesbians; gays; ageing